VP021 A WAY TO TREAT SPIGELIAN HERNIA. (25th November 2021) - Barbosa, Bruno; Pereira, Raquel; Prudente, Cesar; Diogo, Maria Joao; Casimiro, Carlos; Marques, Vitor
Abstract: Aim: "Spigelian hernia is uncommon and accounts for only 0.12–2% of all abdominal hernias. It is mandatory to perform surgical correction and in recent years the laparoscopic approach is gaining ground. The authors pretend to demonstrate a video of an outpatient laparoscopic repair of Spigelian hernia." Material and Methods: "53-year-old woman with a left Spigelian hernia referred to laparoscopic repair via intraperitoneal approach." Results: "The patient was submitted to laparoscopic correction with a Ventralex ® mesh. The surgery went without any complication and under 30 minutes. A few hours after the surgery, the patient was discharged. In the follow-up appointment, the patient had no complaints or evidence of recurrence." Conclusions: "Spigelian hernias are rare and have a mandatory surgical indication. Traditionally, open surgical repair is most commonly used. However, laparoscopic approach is becoming increasingly popular since it allows faster recovery, shorter hospital stay, and less pain, with no commitment to recurrence. Currently, there are no studies that demonstrate the superiority of a laparoscopic technique (intraperitoneal, TAPP or TEP). The intraperitoneal route is a simple, faster, and easily reproducible approach."